Secondary metabolite profiles and anti-SARS-CoV-2 activity of ethanolic extracts from nine genotypes of Cannabis sativa L - Schadich, Ermin; Kaczorová, Dominika; Béres, Tibor; Džubák, Petr; Hajdúch, Marián; Tarkowski, Petr; Ćavar Zeljković, Sanja (Archiv der Pharmazie, 2025)
This study deals with the comprehensive phytochemical composition and antiviral activity against SARS-CoV-2 of acidic (non-decarboxylated) and neutral (decarboxylated) ethanolic extracts from seven high-cannabidiol (CBD) and two high-Δ9-tetrahydrocannabinol (Δ9-THC) Cannabis sativa L. genotypes. Their secondary metabolite profiles, phytocannabinoid, terpenoid, and phenolic, were determined by LC-UV, GC-MS, and LC-MS/MS analyses, respectively. All three secondary metabolite profiles, cannabinoid, terpenoid, and phenolic, varied significantly among cannabinoid extracts of different genotypes. The dose-response analyses of their antiviral activity against SARS-CoV-2 showed that only the single predominant phytocannabinoids (CBD or THC) of the neutral extracts exhibited antiviral activity (all IC50 < 10.0 μM). The correlation matrix between phytoconstituent levels and antiviral activity revealed that the phenolic acids, salicylic acid and its glucoside, chlorogenic acid, and ferulic acid, and two flavonoids, abietin, and luteolin, in different cannabinoid extracts from high-CBD genotypes are implicated in the genotype-distinct antagonistic effects on the predominant phytocannabinoid. On the other hand, these analyses also suggested that the other phytocannabinoids and the flavonoid orientin can enrich the extract's pharmacological profiles. Thus, further preclinical studies on cannabinoid extract formulations with adjusted non-phytocannabinoid compositions are warranted to develop supplementary antiviral treatments.
Keywords: Antiviral Agents; Cannabis; antiviral activity; genotyp; Plant Extracts; ethanol; Ethanol; phytocannabinoids; SARS-CoV-2; Genotype; chemical composition; antivirové látky; SARS‐CoV‐2; Cannabis sativa; rostlinné extrakty